RESTORATIVE ASSESSMENT BASED ON THE RESULTS OF INTEGRATED ASSESSMENT PROSECUTION OF RESTORATIVE JUSTICE ABUSE - Bayu Mediansyah (Cepalo, 2022)
Narcotics Law has ensure rehabilitation medical and social for abuser narcotics. However on level enforcement law , rehabilitation abuser narcotics no as well as immediately done, abuser narcotics must go through the appraisal process more first . In system Justice criminal , stage prosecution hold strategic role. With Thus it is also important to know the appraisal process for abuser narcotics on Step prosecution, because of that, article this will analyze problem in the assessment process addict narcotics on Step prosecution and how optimizing restorative justice in prosecution user narcotics based on recommendation assessment integrate? For answer problem the used method study normative empirical descriptive and qualitative. Research results show that on Step prosecution, there is a number of problem in the assessment process for abuser narcotics, Difference view enforcement law dominate problem this. Settings evaluation integrated have factor strength binding, means, and weak infrastructure, and culture law Public no understand benefit evaluation and more choose criminal prison for abuser narcotics, one approach potential for complete problem this is justice restorative. In Thing this the application of restorative justice is optimized with socialization and education about evaluation user drugs, increase coordination enforcement law, raising funds for implementation assessment, and enhancement facility and facility evaluation user drugs.